Bilateral Ocular Affection Associated with Trypanosoma evansi Infection in German Shepherd Dog: A Case Report - Kumar Gupta, Kapil; Gupta, Neha; Punia, Sunil; Dutta, Nishchal; Sudan, Vikrant (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Trypanosomosis, an arthropod-borne infectious disease  caused by a flagellate protozoan parasite, Trypanosoma  evansi, poses significant economic challenges, particularly  in the tropical regions such as India (Jaiswal et al., 2015).  The disease affects bovines, canines, felines, and camelids.  It is primarily transmitted mechanically by the biting  haematophagous flies, with outbreaks becoming more  frequent during the rainy season due to increased vector  population (Jaiswal et al., 2015). Initially restricted to wild  animals, over the time, disease has spread to the domestic  animals (Sudan et al., 2017). Clinically, trypanosomosis  presents with symptoms such as anorexia, emaciation,  intermittent fever, progressive anaemia, conjunctivitis, limb  edema, and superficial lymphadenopathy (Pandey et al., 2015).  Neurological manifestations, like delirium, head pressing,  ataxia, rear limb paralysis, and tonic-clonic seizures, have also  been reported (Jaiswal et al., 2015; Sudan et al., 2017). Ocular  involvement in canine trypanosomosis is rare, with limited  literature available on the subject (Behera et al., 2017; Abbas  et al., 2021). During disease development the parasites travel  down from brain through optic nerve and causes deposition  of immune complex in aquas humour which clinically results  into development of corneal edema and opacity (Reddy and  Sivajothi, 2017). This case report presents a clinical case of T.  evansi induced ocular manifestations in a German Shepherd  dog and its therapeutic management with diminazene  aceturate in conjunction with supportive therapy.
Keywords: Trypanosomosis; arthropod; borne; infectious; disease